Case Study: analysis of flood adaptation measures through the simulation of an event in the Matina Limón river, Costa Rica - Watson, Fernando (2022)
The proximity of urban and extensive agricultural areas to the rivers of the Atlantic watershed in Costa Rica contrasts with its unstable morphology. Additionally, changes on the rain regime have increased the frequency of natural disasters affecting regularly the nearby populations and the economy of the country. Detailed studies demonstrating the impact of rivers in urban areas and high agricultural activity are necessary to establish adequate flood mitigation and control measures. The present study shows a case study of the impact of a 25-year flood event on the flood plain of the Matina River in Costa Rica, by means of a bi-dimensional hydraulic modelling with the aim to contribute to the adequate management of land use and the establishment of protection measures in the study vregion. A digital elevation model, of the topography of the study area, obtained with a LIDAR device, and the estimation of the instantaneous peak flow was obtained with the statistical Weibull distribution for a return period of 25 years, allowed to provide satisfactory information for the flood analysis of complex combinations for surface drainage management. Two scenarios for flood management were analyzed: 1) increasing the dike height, and 2) early opening of an additional mouth at the river outlet during the flood events. The study demonstrated that none of the options were technically feasible and that decision makers should explore other flood mitigation alternatives.